2023
DOI: 10.1161/circulationaha.123.064003
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Frailty on the Efficacy and Safety of Intensive Blood Pressure Control: A Post Hoc Analysis of the SPRINT Trial

Abstract: BACKGROUND: Frailty is associated with an increased risk of all-cause death and cardiovascular events. However, it is uncertain whether frailty modifies the efficacy and safety of intensive blood pressure control. METHODS: Data from SPRINT (Systolic Blood Pressure Intervention Trial) were used to construct a frailty index. Subgroup differences in intensive blood pressure control treatment effects and safety outcomes were measured on a relative and an ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“… 5 However, a post hoc analysis of the SPRINT indicated that frail individuals can benefit from intensive BP control without elevated risks of SAE. 6 Hence, it is crucial to identify suitable metrics for evaluating BP control efficacy in patients with hypertension and high cardiovascular risk, which will optimize pharmacological treatment strategies and guide future clinical trials aimed at enhancing prognostic outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 5 However, a post hoc analysis of the SPRINT indicated that frail individuals can benefit from intensive BP control without elevated risks of SAE. 6 Hence, it is crucial to identify suitable metrics for evaluating BP control efficacy in patients with hypertension and high cardiovascular risk, which will optimize pharmacological treatment strategies and guide future clinical trials aimed at enhancing prognostic outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Model 1 remained unadjusted, while Model 2 accounted for all relevant baseline variables: age, gender, race, BMI, 19 smoking status, 20 baseline SBP, 21 baseline DBP, 22 previous CVD, 23 the number of BP‐lowering agents, 24 intensive treatment, 25 the Framingham 10‐year CVD risk score, 26 and frailty index (FI). 6 The selection of variables was determined based on their relevance to the outcomes, guided by clinical experience and a comprehensive review of the literature. Additionally, a restricted cubic spline curve (RCS) was constructed based on the principles of model 2.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hypertension was considered the most important independent risk factor predicting mortality in frail patients ( 48 ). The Systolic Blood Pressure Intervention Trial (SPRINT) study demonstrated that frail patients benefited from intensive blood pressure control without an increased risk of serious adverse events ( 46 ). Therefore, efforts are needed to recognize frailty in the elderly population, and interventions to limit or reverse frailty may reduce the incidence of adverse cardiovascular events and prolong survival expectations in frail older adults.…”
Section: Discussionmentioning
confidence: 99%
“…Frailty is a common geriatric syndrome among the elderly. The prevalence of frailty in the elderly population ranges from 16% to 26.7% (45)(46)(47). Frail older adults have higher rates of mortality and various diseases, especially cardiovascular diseases such as hypertension, diabetes, and heart failure.…”
Section: Discussionmentioning
confidence: 99%